Euthanasia: Islamic perspective - Malik, Mohammad Manzoor (IIUM Press, 2011)
Euthanasia is conceptually analyzed and various relevant issues are categorized under active and passive euthanasia. Furthermore, a formulation of an Islamic perspective is sought on the basis of the Quran and Sunnah and their understanding in relation to the issue that has appeared in the form of Islamic medical codes, resolutions of Muslim jurisprudential bodies, and in various fatwas from many eminent Muslim scholars. The study shows that there are two types of euthanasia: active and passive. On the materials analyzed, active euthanasia includes voluntary, involuntary, non-voluntary euthanasia, and physician-assisted suicide. Their impermissibility is demonstrated on the basis of the Quran and Sunnah. Regarding the second type of euthanasia called as passive euthanasia, the issues which could be grouped under it are withholding, withdrawing, and refusing medical treatment; Do Not Resuscitate (DNR); discontinuing life support system; starvation and dehydration; and pain medication that may hasten death as a side effect. The study concludes that in special circumstances all these acts are permissible; however starvation which includes discontinuing feeding tubes and hydration is not permissible.